Makhṭūṭah Anis al-Muttaqīn li al-Shaikh al-Malik al-Fard ʿAbdu al-Ṣamad bin Faqīh Ḥussain bin Faqīh Muḥammad - Nita Zakiah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This research examines a manuscript written by Shaikh Al-Malik Al-Fard ʽAbdu Al-Ṣamad Ibn Faqīh Ḥussein Ibn Faqīh Muḥammad. The study was divided into a description of the manuscript, transcribing the copy into the Malay language, and realizing the text and the essential ideas contained in the text. The objectives achieved are to present a representative edit of the text, to reveal the moral teachings in the text, and to explain the possibility of moral values that are relevant to present and future life. The research methodology used was philological research, data collection tools by conducting observations and recording. The steps of philological research include: determining research targets, inventorying manuscripts, statements, and manuscript descriptions, transliterating manuscripts, editing and translating texts, as well as summaries of the contents of the manuscripts and content analysis.تبحث هذه الدراسة في المخطوطة التي كتبها الشيخ الملك الفرد عبد الصمد بن فقيه حسين بن فقيه محمد. تم تقسيم البحث إلى وصف المخطوطة، ونسخ النسخة إلى اللغة الملايوية، وإدراك النص والأفكار المهمة الواردة في النص. الأهداف التي تم تحقيقها هي تقديم وتعديل تمثيلي للنص، للكشف عن التعاليم الأخلاقية في النص، وشرح إمكانية القيم الأخلاقية ذات الصلة بالحياة الحالية والمستقبلية. ومنهجية البحث المتبعة، والبحوث اللغوية، وأدوات جمع البيانات تمت بإجراء الملاحظات والتسجيل. تشمل خطوات البحث اللغوي: تحديد أهداف البحث، وجرد المخطوطات، والملاحظات، وأوصاف المخطوطات، وترجمة المخطوطات، وتحرير النصوص وترجمتها، بالإضافة إلى ملخصات محتويات المخطوطات وتحليل محتواها.